Consumer acceptance of patient‐performed mobile teledermoscopy for the early detection of melanoma. (1st December 2016) - Horsham, C.; Loescher, L.J.; Whiteman, D.C.; Soyer, H.P.; Janda, M.
Summary: Background: Mobile teledermoscopy allows consumers to send images of skin lesions to a teledermatologist for remote diagnosis. Currently, technology acceptance of mobile teledermoscopy by people at high risk of melanoma is unknown. Objectives: We aimed to determine the acceptance of mobile teledermoscopy by consumers based on perceived usefulness, ease of use, compatibility, attitude/intention, subjective norms, facilitators and trust before use. Consumer satisfaction was explored after use. Methods: Consumers aged 50–64 years at high risk of melanoma (fair skin or previous skin cancer) were recruited from a population‐based cohort study and via media announcements in Brisbane, Australia in 2013. The participants completed a 27‐item questionnaire preteledermoscopy modified from a technology acceptance model. The first 49 participants with a suitable smartphone then conducted mobile teledermoscopy in their homes for early detection of melanoma and were asked to rate their satisfaction. Results: The preteledermoscopy questionnaire was completed by 228 participants. Most participants (87%) agreed that mobile teledermoscopy would improve their skin self‐examination performance and 91% agreed that it would be in their best interest to use mobile teledermoscopy. However, nearly half of participants (45%) were unsure about whether they had complete trust in the telediagnosis. The participants who conducted mobile teledermoscopy ( n = 49) reported that the dermatoscope was easy to use (94%) and motivated them to examine their skin more often (86%). However, 18% could not take photographs in hard‐to‐see areas and 35% required help to submit the photograph to the teledermatologist. Conclusions: Mobile teledermoscopy consumer acceptance appears to be favourable. This new technology warrants further assessment for its utility in the early detection of melanoma or follow‐up.